(untitled) (Philological Studies, 2019)
The article deals with sociolect as a means of intercultural communication on the example sites from the Internet to show the presence of associations, which are to communicate using the language options. Identified ways of overcoming the barrier of misunderstanding in intercultural communication, which includes contacts between speakers of different national cultures, but gender, age, corporate.